Maternal Self-Efficacy of Pregnant Indonesian Teens: Development and Validation of an Indonesian Version of the Young Adult Maternal Confidence Scale and Measurement of Its Validity and Reliability. (30th November 2017) - Wardani, Desy Ayu; Rachmawati, Imami Nur; Gayatri, Dewi
ABSTRACT: Pregnant teens often feel uncertain in the last trimester about their ability to take care of their baby. At this time, maternal confidence in the ability to care for the baby is an important step in the preparation for becoming a mother. The purpose of this study was to examine the validity and reliability of an Indonesian version of the Young Adult Maternal Confidence Scale (YAMCS) as an instrument to measure maternal self-efficacy of pregnant teens in the last trimester. The study consisted of 90 pregnant teens, age of respondents less than 19 years and living in 1 of 3 sub-districts: Cilember, Sukamanah and Megamendung, Bogor Regency. West Java. All the participants completed a questionnaire based on the YAMCS to assess maternal self-efficacy. The YAMCS consists of 3 dimensions (perception of ability, uncertainty, and mothering behaviors) and 10 items. All items of the YAMCS had corrected item-total item correlation more than 0.3 and had 0.859 Cronbach's α scores. Based on the findings of this study, this questionnaire is a valid and reliable measure of maternal self-efficacy of pregnant teens in Indonesia. Health workers can use the questionnaire to assess the confidence of pregnant women, especially that of adolescents, in caring for their baby and being a good mother.